Civil Society in Algeria ... between the Voluntary Content and the Political Goal - Zoubiri, Abdallah (Journal of Legal Studies and Researches, 2021)
This research paper tries to study the reality of civil society, in a watershed stage that Algeria knows about a fundamental change affecting society and some of its structures of social, economic, political and cultural relations, analyzing the framework that governs the work of these organizations and monitoring the most prominent political developments in an attempt to formulate a new political scene. This made it possible to see changes in principles as part of the development of civil society and its self-initiatives and proposals. Also an attempt to monitor his roles, the expansion of his influence, and the mechanisms of his political influence.